Enhanced Degradation of Oxytetracycline Antibiotic Under Visible Light over Bi2WO6 Coupled with Carbon Quantum Dots Derived from Waste Biomass - Ren, Haitao; Qi, Fan; Zhao, Ke; Lv, Du; Ma, Hao; Ma, Cheng; Padervand, Mohsen (Molecules (Basel, Switzerland), 2024)
Improving the photogenerated carrier separation efficiency of individual semiconductor materials has always been a key challenge in photocatalysis. In this study, we synthesized a novel photocatalytic material, N-CQDs/UBWO, in situ by combining nitrogen-doped carbon quantum dots (N-CQDs) derived from discarded corn stover with ultrathin Bi2WO6 nanosheets (UBWO). Detailed characterization indicates that the random distribution of N-CQDs on the UBWO surface increases the specific surface area of UBWO, which is beneficial for the adsorption and degradation of oxytetracycline (OTC). More importantly, N-CQDs act as electron acceptors, promoting the effective separation of photogenerated charges, prolonging the lifetime of charge carriers in UBWO, and thereby enhancing the degradation efficiency of OTC. As a result, the optimized 3wt%N-CQDs/UBWO could degrade 85% of OTC within 40 min under visible light, with a removal rate four times that of pure Bi2WO6. The performance of photocatalytic degradation over OTC by 3wt%N-CQDs/UBWO exceeds that of most reported Bi2WO6-based photocatalysts. The EPR analysis confirmed that ∙O2− and ∙OH are the main active species in the photocatalytic degradation of OTC on 3wt%N-CQDs/UBWO. This study provides insight into designing green, low-cost, and efficient photocatalysts using CQDs derived from waste biomass and the degradation of emerging pollutants like antibiotics.